Location of paper sorting center for schools in Vila Mariana, São Paulo - Soares, Isabela Rubim Costa; Biagio, Marina Gutierres; Gonçalves, Max Filipe Silva; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2020)
The citizen's profile has changed in relation to the impacts caused by high consumption and the incorrect disposal generated by its waste; As a result, citizens have continuously sought solutions that minimize the impacts of their actions. Thus, the present study aimed to identify the best location for the installation of the Sorting Center link for the reverse logistics of paper chips generated in schools in the Vila Mariana neighborhood, taking into account the decision variables. Through the chosen methodology, the following specific objectives were defined: mapping schools in the Vila Mariana neighborhood, in the city of São Paulo; identify the decision variables that influence and should be taken into account to determine the estimates; evaluate the installation of a Sorting Center to serve the region using a location model, center of gravity. Considering the method chosen, schools in the region were mapped, making it possible to define the best location for the Sorting Center, as well as to evaluate its installation according to the criteria of volume of paper chips generated by the mapped schools, cost of transporting the waste from schools to the Sorting Center and the distance between schools and the Sorting Center.
Keywords: Sorting Center; Reverse logistic; Paper; Urban solid waste